The Effect of Water Content to Soil Tillage - Wirosoedarmo, Ruslan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The aim of the research was to find out the effect of water content on the soil friability and to determine the appropriate soil water content for tillage. The soil samples were taken from Balai Benih Induk Palawija, Bedali, Lawang, Malang Regency and measurements of parameters were carried out at the Laboratory of Agricultural Power and Machinery, Faculty of Agricultural Technology, Brawijaya University, Malang from June until July 2002. The parameters used are the compression strength of soil taken from a number of soil volumes and the water contents. The results indicated that the soil strength was significantly affected by the water content as well as a combination of the water content and the volumes of soil aggregates. The reduction of volumes of soil aggregates due to decreasing of soil water content caused an increase in the soil strength. The value of soil strength ranges from 7,19 kPa to 166,39 kPa. The friability of Bedali soil was achieved in the range of soil water content: 20 – 26 % with a soil friability index (k) of 0,25-0,27.